Expression of MICA in Zero Hour Biopsies Predicts Graft Survival After Liver Transplantation - Resch, Thomas; Hackl, Hubert; Esser, Hannah; Günther, Julia; Schwelberger, Hubert; Ritschl, Paul Viktor; Ebner, Susanne; Maglione, Manuel; Mellitzer, Vanessa; Biebl, Matthias; Öllinger, Robert; Zoller, Heinz; et al. (Frontiers in Immunology, 2021)
In search for novel biomarkers to assess graft quality, we investigated whether defined candidate genes are predictive for outcome after liver transplantation (LT). Zero-hour liver biopsies were obtained from 88 livers. Gene expression of selected candidate markers was analysed and correlated with clinical parameters as well as short and long-term outcomes post LT. Whereas both, the calculated Eurotransplant Donor-Risk-Index and the donor body mass index, had either a poor or no predictive value concerning serum levels indicative for liver function (ALT, AST, GGT, bilirubin) after 6 months, chronological donor age was weakly predictive for serum bilirubin (AUC=0.67). In contrast, MICA demonstrated a high predictive value for serum liver function parameters revealing an inverse correlation (e.g. for ALT: 3 months p=0.0332; 6 months p=0.007, 12 months 0.0256, 24 months p=0.0098, 36 months, p=0.0153) and proved significant also in a multivariate regression model. Importantly, high expression of MICA revealed to be associated with prolonged graft survival (p=0.024; log rank test) after 10 years of observation, whereas low expression was associated with the occurrence of death in patients with transplant related mortality (p=0.031). Given the observed correlation with short and long-term graft function, we suggest MICA as a biomarker for pre-transplant graft evaluation.